The presence of a DNA binding complex correlates with E beta class II MHC gene expression. - Finn, P W (1990)
The class II major histocompatibility complex (MHC, Ia) antigens are a family of membrane proteins whose expression is strictly regulated. They have a limited tissue distribution and their expression is regulated both developmentally and in response to external stimuli. Here we report the identification of a DNA binding protein complex (termed complex A) within the murine E beta MHC gene, which is restricted to cells that express Ia antigens. Complex A binding activity is developmentally regulated in cells of the B lineage in accordance with class II expression and is responsive to two different Ia-inducing lymphokines, interferon-gamma in macrophages and interleukin-4 in pre-B cells. The DNA target sequence in complex A includes three previously defined transcriptional motifs W, X and Y, and acts as a cis-acting transcription element. Complex A is present both in cells that are constitutive for class II MHC expression and in cells that have been induced for class II MHC expression. These results suggest that complex A may play a critical role in the regulation of class II MHC gene expression.